More milk, thanks to oil seeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A cattle feed supplement that significantly raises milk production has been developed during a 3-year joint research effort between the Australian Commonwealth Scientific and Industrial Research Organisation (CSIRO) and India's National Dairy Development